Achieving agroecological food system transformation - Fuchs, Lisa Elena; Awiti, Alex; Nyawira, Sylvia; Chege, Christine G. Kiria; Guettou Djurfeldt, Nadia (2025)
While agroecological solutions exist at farm level, scaling them to broader food, land and water systems entails many hurdles. The CGIAR Initiative on Agroecology was launched in order to clear them. Based on their experience in Kenya, our authors share some overarching insights. A redesign of food systems is urgently needed to achieve ecological, economic and social sustainability. Agroecology offers a transformative pathway that integrates sustainable and resilient agricultural practices with increased agency for smallholder farmers and other food system actors, and pays special attention to women, youth and other marginalised groups. Agroecological solutions are well documented at farm level, but applying them to broader food, land and water systems remains a challenge given insufficient evidence, misaligned policies, inadequate capacity, insufficient attention to intersecting inequalities and limited financing mechanisms. The CGIAR Initiative on Agroecology (see Box) has been aiming to address these barriers by promoting the application of contextually appropriate agroecological principles by food system actors such as farmers, businesses, government entities and policy-makers in so-called agroecological living landscapes (ALLs). The latter are geographically bounded landscapes in which farmers, agroecology practitioners, researchers and other development actors identify, test and promote agroecological innovations across sectors and scales, thus generating evidence on the transformative potential of agroecology and identifying institutional innovations. As we come to the end of a three-year cycle of collaborative implementation and transition to a new CGIAR Science Program on Multifunctional Landscapes, the Agroecology Initiative Kenya research team leads share the following nine key messages.